The use of the challenge test to analyse preservative efficiency in non-sterile cosmetic and health products: applications and critical points - Fiorentino, F. A. M. [UNESP]; Chorilli, Marlus [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Royal Soc Chemistry, 2011)
Here we review the challenge test, which is used to evaluate the efficiency of preservatives in non-sterile cosmetic products. We describe the historical context, explain the technique and interpretation of the results according to pharmacopoeias and emphasise the critical points of the technique. In order for microbial growth to occur, non-sterile formulations must have water, minerals and vitamins in addition to other nutrients. The challenge test is a useful guide regarding the type and amount of preservatives to be added to a product to ensure its quality. This technique can also be used to analyse the efficiency of the product packaging and whether it prevents microbial contamination. This method is used in security and stability tests during product development, but it is not routinely performed as a control. Although there is no consensus regarding its use, this test is the most suitable to analyse preservative effectiveness.